The Role of Tahir Malik’s Works in Youth Education - Boysarovna, Ismailova Marhabo; Mukhtorovna, Porsieva Zamira (Researchparks Publishing, 2023)
Tahir Malik, the greatest writer of our nation, gained fame with his works of greetings. This article discusses the importance of the writer's works in the education process of young people.